2021
DOI: 10.1002/csc2.20479
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of grain yield and resistance of extra‐early‐maturing maize inbreds to northern corn leaf blight

Abstract: Maize (Zea mays L.) is a food security crop in sub‐Saharan Africa (SSA). Incidence of northern corn leaf blight (NCLB), caused by Exserohilum turcicum, in lowlands of SSA during the past decade has caused 30–70% reduction in maize yield. This study (a) examined the combining abilities of extra‐early maize (EEM) inbreds and classified them into heterotic groups; (b) elucidated gene action controlling resistance to NCLB; (c) assessed grain yield (GYLD) and yield stability of EEM hybrids under NCLB infection; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Similarly, the NLB is favoured by mild temperatures (15–25°C), high relative humidity (90%–100%), extended periods of leaf wetness, and frequent light showers as noticed by Ogliari et al (2007). It had also been reported that the distribution and development of NLB is favoured by long dew periods, and cool to moderate temperatures with high relative humidity across maize‐growing areas of the world (Ahangar et al, 2022; Badu‐Apraku et al, 2021). Hence, extreme impact of leaf blight on maize in the mid‐ and high‐land agro‐ecologies of Uganda, Kenya, Ethiopia, Zambia and South Africa have been reported (Ramathani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the NLB is favoured by mild temperatures (15–25°C), high relative humidity (90%–100%), extended periods of leaf wetness, and frequent light showers as noticed by Ogliari et al (2007). It had also been reported that the distribution and development of NLB is favoured by long dew periods, and cool to moderate temperatures with high relative humidity across maize‐growing areas of the world (Ahangar et al, 2022; Badu‐Apraku et al, 2021). Hence, extreme impact of leaf blight on maize in the mid‐ and high‐land agro‐ecologies of Uganda, Kenya, Ethiopia, Zambia and South Africa have been reported (Ramathani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such environmental conditions may support sporulation and conidia germination, infection, establishment and development of NLB in maize. Other studies also reported that epidemic of NLB is influenced by weather variables, among other factors (Ahangar et al, 2022;Badu-Apraku et al, 2021;Camera et al, 2019;Wathaneeyawech et al, 2015).…”
Section: Independent Variable Dfmentioning
confidence: 93%
See 2 more Smart Citations
“…The photosynthetic potential of maize is significantly reduced by E. turcicum infection and this invariably affects grain yield [ 22 ]. The premature death of infected plants has been reported when the disease epidemic begins at an early stage [ 11 , 23 ]. This is consequent upon the alteration of the physiological activities of the infected host [ 24 ].…”
Section: Introductionmentioning
confidence: 99%